Certain fractional calculus and integral transform results of incomplete ℵ‐functions with applications. (28th February 2020) - Kumar Bansal, Manish; Kumar, Devendra; Nisar, K. S.; Singh, Jagdev
Abstract : In this paper, we study certain interesting and useful properties of incomplete ℵ ‐functions. The incomplete ℵ ‐function is an extension of the ℵ ‐function. We find several useful classical integral transforms of these functions. Further, we examine the fractional calculus with the incomplete ℵ ‐functions and point out several special cases. Finally, we give the applications of incomplete ℵ ‐functions in detecting glucose supply in human blood.